Cluster Analysis for Better Segmentation: A Study on Branded Female Personal Care Products - Rani , T. Suchitra (Gyan Management Journal, 2010)
Consumer behavior is quickly gaining new ground over the years. This has become even more relevant the present day world, marked up by rapid changes in the lifestyles, demographics and social status. It holds great interest for manufacturers, advertisers, research agencies, consumers and students of human behavior. Understanding Consumer Behaviour starts with segmentation. With changes in lifestyle, the Indian personal care market has been showing healthy growth rates in recent years. The preference of Indian consumers is changing from the 'merely functional' products to more 'advanced and specialized' cosmetic items. When clustering is applied to data that describes customer buying habits, gender, age, income, etc. it helps in discovering distinct groups in their customer base. This will help marketers to customize their marketing and product development strategy to each consumer group to increase sales and build brand loyalty.
Keywords: Personal care products; Skin Care Product; Hair Care products; Value conscious customers; price conscious customers